Essential Components Of Effective Reading Instruction: Major Investigation Of Special Education Teachers’ Erudition (Journal of Namibian Studies : History Politics Culture, 2023)
The National Reading Panel has identified phonemic awareness, phonics, fluency, vocabulary, and reading comprehension as the five essential components for initiating reading instruction. Teachers’ knowledge of these components can influence teaching approaches and contribute to students’ learning outcomes at the beginning of reading stage. This study examined the knowledge of the five Essential Components of Effective Reading Instruction (ECERI) with 184 Special Education Teachers (SET) who handle diverse students from different special education categories. The results indicated that the level of performance of SET in the ECERI scale was low, with a relatively high score in the reading comprehension and vocabulary component. The results also showed statistically significant correlations with the score of phonemic awareness and fluency with a high level of SET knowledge. The phonics, vocabulary, and reading comprehension component showed no statistically significant correlations with a high level of SET knowledge. The results revealed that a higher score of knowledge was more correlated with teachers who teach autism, while no statistical significance was observed in the results of SET on the scale of the categories of teaching disabilities. Moreover, the variable of gender and teaching experience had negative correlations with high scores of SET knowledge. Therefore, no statistically significant differences emerged. In SET, lack of knowledge concerning the components of reading specifies the urgent need for training programs on those topics to boost their teachers’ cognitive and teaching skills.